2023
DOI: 10.3389/fnimg.2023.1110258
|View full text |Cite
|
Sign up to set email alerts
|

Review: The use of functional magnetic resonance imaging (fMRI) in clinical trials and experimental research studies for depression

Abstract: Functional magnetic resonance imaging (fMRI) is a non-invasive technique that can be used to examine neural responses with and without the use of a functional task. Indeed, fMRI has been used in clinical trials and pharmacological research studies. In mental health, it has been used to identify brain areas linked to specific symptoms but also has the potential to help identify possible treatment targets. Despite fMRI's many advantages, such findings are rarely the primary outcome measure in clinical trials or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…Employing multi-modal data will also enhance our understanding of the causal pathways in MDD. Finally, the use of drugs will also have an impact on the research results [62,63]. In subsequent studies, drug factors should be excluded as much as possible to ensure the quality of the research.…”
Section: Discussionmentioning
confidence: 99%
“…Employing multi-modal data will also enhance our understanding of the causal pathways in MDD. Finally, the use of drugs will also have an impact on the research results [62,63]. In subsequent studies, drug factors should be excluded as much as possible to ensure the quality of the research.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the processing of basic emotions, activation likelihood estimation meta-analyses of functional neuroimaging studies concluded that the amygdala reacts in particular to fearful stimuli (Vytal and Hamann, 2010), however, other studies have indicated responsiveness also to positive emotions (Costafreda et al, 2008). Clinically, functional alterations of the amygdala are assumed to play an important role in affective disorders, and there is growing interest in using magnetic resonance imaging (MRI) -derived biomarkers from both task-based and resting-state functional MRI (rs-fMRI) to track the modulatory influence of pharmacological, but also behavioral interventions in these patient groups (Malejko et al, 2017;Kotoula et al, 2023). However, current knowledge on the acute and chronic effects of exercise on the function of affect-related brain networks is still limited.…”
Section: Introductionmentioning
confidence: 99%